Phytochemicals Studies on J. prostrata and J. aurea - KUMAR SRIVASTAVA, SHARAD; BAHADUR, FATEH (Asian Journal of Chemistry, 2010)
The antioxidant and hepatoprotective activity of J. prostrata and J. aurea have been investigated. Ethanolic extract of J. prostrata (100 mL/kg p.o. for 7 d) provided hepato protection against CCl4 by significantly decreasing SGPT and SGOT levels to 272.63 ± 5.26 and 98.16 ± 3.50, respectively which were comparable to nirocil (p < 0.02, p < 0.05) found in Phyllanthus amarus (P. niruri).